PELATIHAN PEMBUATAN MAS DUPA KEPADA POKTAN DESA RINDU HATI KABUPATEN BENGKULU TENGAH - Rahmawati, Suci; Komala Sari, Delia; Ramadhani, Nurfijrin; Sartati, Juwita; Monica, Thesa; Yestira, Triyana (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The Farmers group (Poktan) in Rindu Hati Village, Central Bengkulu Regency, Bengkulu Province is one of the groups that received guidance from University of Bengkulu in papaya cultivation. This Community Service Activity (PPM) was aimed to provide skill in formulated MAS DUPA (Papaya Leaf Mask) for Rindu Hati Village . This activity was carried out on August 9, 2021 with 25 participants. The methods used in this PPM activity are debriefing theory, discussion, demonstration and practice. The results were evaluated using a questionnaire in the form of question sheet and satisfaction survey to measure the level of satisfaction and understanding of participants about theory and practices that provided by the service team. The question sheet consists of 10 questions given before and after activity. The results were showed that increases participant understanding which indicated by increases in the average quiz score of participants from 79.38 to 92.5. For the results of satisfaction survey, it can be seen that 68% are very satisfied, 32% are satisfied and 0% are less satisfied and dissatisfied. This activity is expected to help poktan in optimizing the processing of papaya cultivation and can increase their economy.